"So I Just Applied” : Understanding the journey to student government participation (Higher Education Politics and Economics, 2025)
The purpose of this narrative inquiry is to better understand why students in higher education are motivated to get involved in student government. We analyzed the responses of ten current student government leaders at public regional comprehensive institutions in the United States. The analysis is guided by Astin's theory of student involvement and the social change model of leadership development. The study finds that many leaders did not initially plan to engage in student government, emphasizing the impact of past civic involvement, current student engagement, and peer invitations on their subsequent student government participation. Implications call for institutions to deepen their understanding of enrolled students and provide accessible avenues for leadership development.